2012
DOI: 10.1177/0093854812455741
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of a General Risk/Needs Assessment Inventory on Sexual Offender Recidivism and an Exploration of the Professional Override

Abstract: This study examines the predictive validity of the Level of Service/Case Management Inventory (LS/CMI) on a sample of sexual offenders extracted from a large cohort of offenders and compares predictive validities with nonsexual offenders from the same cohort. The LS/CMI predicted sex offenders' general recidivism, which occurred at a rate of 44.1%, with about the same accuracy as less frequently occurring violent (12.34%) and sexual recidivism (3.73%; AUC = .77, .74, and .74, respectively) and with nonsexual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
140
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(172 citation statements)
references
References 53 publications
24
140
3
5
Order By: Relevance
“…The remaining sections produced weak associations with recidivism. Wormith, Hogg, and Guzzo (2012) found the Specific Risk/Need section to highly correlate with general recidivism among sex offenders, but less so for violent outcomes. The other sections had significant correlations, but the magnitude of their associations was markedly reduced.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The remaining sections produced weak associations with recidivism. Wormith, Hogg, and Guzzo (2012) found the Specific Risk/Need section to highly correlate with general recidivism among sex offenders, but less so for violent outcomes. The other sections had significant correlations, but the magnitude of their associations was markedly reduced.…”
mentioning
confidence: 88%
“…Although they are normally interpreted qualitatively, a scoring procedure was adopted in which all items marked as "yes" were summed to generate section and subscale totals. This scoring procedure has been used in past research (i.e., Girard & Wormith, 2004;Wormith et al, 2012). Note.…”
Section: Materials Ls/rnrmentioning
confidence: 99%
“…Brews, 2009;Rettinger & Andrews, 2010;Wormith, Hogg, & Guzzo, 2012) and with mentally disordered offenders specifically (Girard & Wormith, 2004;Skeem et al, 2014). In a recent meta-analysis of 128 studies comprising 137,931 offenders, Olver, Stockdale, and Wormith (2014) reported the LS scales to significantly predict general and violent recidivism (r = .29 and .23, respectively); these effects were upheld across gender and ethnicity.…”
Section: Level Of Service/case Management Inventorymentioning
confidence: 99%
“…A number of studies demonstrate practitioners tend to overwhelmingly escalate the prediction of risk for those convicted of sexual offences, to excessive levels (Ansbro, 2010;Wormith, Hogg, & Guzzo, 2012). The RM2000 classifications for this present study do not appear to have been included in the decision making of the risk management strategies developed as part of the clients risk management planning, or were at least not recorded as such.…”
Section: Discussionmentioning
confidence: 88%